KONJUNGSI DALAM LAGU-LAGU POPULER PADA DUA RENTANG WAKTU YANG BERBEDA - Eka Putra, Reza Ramanda (Universitas Negeri Surabaya, 2019)
From the perspective of sociolinguistic, people and language are tightly connected. People are changing not the language. The way people used language now and then are different, even just slightly. Words which then considered prestigious are not necessarily the same today. Then, talking about song, the lyrics which used now and then are different too. A song can be called popular if it can be accepted by many people, and then it can be mean that the language or lyric used in the popular song, as a part of the song, is well liked by many people. By using that concept, the researcher compares two languages from two different times. This research is aimed to describe the different use of conjunction between two eras. The researcher uses observation method and noting technique, and data are the conjunctions taken from the songs from two eras which later be compared. The result shows that there are differences. Generally, both eras heavily used subordinate conjunction, but different in percentage. The unique thing is that both eras almost have similar graphics when both are compared.